ASSESSMENT OF THE MOST RELEVANT CAUSES FOR TRANSFER OR DROP-OUT OF MALE SWIMMERS AGED BETWEEN 7 AND 12 YEARS OLD OF “ESTRELA DO OESTE CLUBE” OF DIVINOPOLIS / MG CITY. (Fiep Bulletin - online, 2013)
A growing number of children leave swim training early when they take on the practice of competitive sports too early.The reasons for this are complex and varied. This study intends to identify the most important causes that lead to the drop-out ortransfer of male swimmers aged between 7 and 12 years of Estrela do Oeste Clube from Divinópolis city (Minas Gerais). Thesample consisted of 40 athletes in the aforementioned age group. A questionnaire of 19 closed questions addressing the reasonswhich contribute to the abandonment or transfer of the sport, an informed consent clause, the authorization of the club and theauthorization of parents or guardians. From the questionnaire it can concluded that discouragement is due to overtraining, coldwater at winter time, physical fatigue, mental and emotional, and pressure from parents and coaches to sports's practice. Theseare important reasons for the abandonment of swimming. These reasons teach us to respect the child's learning cycle and avoidtraining that does not match his ability. This way the child does not get tired of training or does not feel unable to carry it outcompletely. In the training, his autonomy and confidence must be worked, giving him opportunity to get to know his capabilitiesand limits, learning when to stop, respecting his development, telling the child what to expect from his training and increase hisinterest in the sport.
Keywords: swimming; relevant reasons; drop out